Current applications of high-frequency ultrasonography in dermatology - Polańska, Adriana; Dańczak-Pazdrowska, Aleksandra; Jałowska, Magdalena; Żaba, Ryszard; Adamski, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
The era of ultrasounds in dermatology started in 1979, when pioneering use of 15 MHz by Alexander and Miller in measuring the skin thickness was introduced. Since then, some new applications of high-frequency ultrasonography (HF-USG) have emerged providing the clinicians with an extra hand in their everyday practice. The main advantages of HF-USG include the possibility of real-time imaging, measurements of morphological and physiological aspects of the skin, safety associated with the use of non-ionizing media as well as the lack of contraindications to its performance. Currently the main clinical use of HF-USG in dermatology regards preoperative assessment of the depth of invasion in melanomas and basal cell carcinomas. The ultrasound image analysis allows noninvasive follow-up of inflammatory skin diseases, like atopic dermatitis, psoriasis and may be used for monitoring effectiveness of therapy in skin lymphomas and sclerotic skin diseases.